Development of Rabin’s Choice Coordination Algorithm in Event-B - Yilmaz, Emre; Hoang, Thai Son (Electronic Communications of the EASST, 2011)
The paper reports our investigation on tool support for the integration of qualitative probabilistic reasoning into Event-B. In the process, we formalise a non- trivial algorithm, namely Rabin’s choice coordination. Our correctness reasoning is a combination of termination proofs in terms of probabilistic convergence and standard invariant techniques. Moreover, we describe how qualitative probabilistic reasoning can be maintained during refinement.